PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA SISWA MI MANGGARUPI GOWA - Alfiani, Fikri; Sukmawati, Sukmawati; Rukli, Rukli (Universitas Pakuan, 2021)
THE INFLUENCE OF THE CREATIVE PROBLEM SOLVING LEARNING MODEL ON THE PROBLEM SOLVING ABILITY OF MI MANGGARUPI GOWA STUDENTSThis study aims to determine the effect of the Creative Problem Solving Learning Model on the mathematical problem solving ability of the students of MI Manggarupi Gowa. This research is a quantitative research with a quasi-experimental type of research. The sample in this study was class VI-A as the experimental class and VI-B as the control class. The test instrument used to determine the students' mathematical problem solving ability is to use a test in the form of a description. The results of data analysis of students' mathematical problem solving abilities in the experimental class pretest obtained an average value of 32.69 and in the control class an average value of 32.56 was obtained. The results of data analysis in the posttest experimental class showed that students' mathematical problem solving abilities increased with an average value of 81.8 while in the control class an average value of 77.5 was obtained. Based on data analysis using one-way ANKOVA, the sig value was obtained. = 0.014. sig value. The results obtained are less than 0.05, i.e. 0.014 0.05, which means that there is a significant difference where the mathematical problem solving ability of students in the class using the Creative Problem Solving Learning Model is higher than the class using Direct Instruction learning after controlling for initial abilities.